Dampak Kewarganegaraan Ganda Bagi Warga Indonesia - Lala Anggina Salsabila; Putri Handayani; Siti Anisah Nasution; Syarifa Aini; Bryan Yamolala Ndruru; Rahmat Fitra; Fazli Rachman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
In Indonesia, every individual has the right to citizenship status, as regulated in Article 28D Paragraph 4 of the 1945 Constitution which states that